RELATIONSHIP MARKETING OUTCOME DALAM KONTEKS PENDIDIKAN TINGGI: PERAN KOMITMEN AFEKTIF, SERVICE CO-CREATION DAN STUDENT ENGAGEMENT - Tjahyadi, Rully Arlan; Kristiawan, Allen; gunawan, ika (Universitas Pendidikan Indonesia, 2021)
Higher Education (HE) efforts in creating value demonstrate its commitment to increasing their competitive way in the education market. Academic quality, improving quality, increasing rankings, and increasing brand value (brand value) are strategies that can be carried out to achieve that ranking. It is also necessary to consider other aspects from the emotional side as a source of organizational success when students as the main customers and the development of long-term relationships with customers is very important for the HE. Customer-oriented has become a central topic in the concept of relationship marketing. Customer loyalty is a concept that is a fundamental relational marketing outcome or it can be implemented as a result of relationship marketing (the result of relationship marketing). This study will focus on variables related to emotional dimensions that contribute to the development of long-term relationships with customers in the context of HE. Specifically, this study will examine the effect of variables, commitment, service creation and engagement on student loyalty. The study results show that customer commitment and engagement affect customer loyalty.